Running Biomechanics increase efficiency, strength & speed - Brandon, R.; Brice, P.; Fyfe, S.; Lancaster, M.; van Rensburg, A.; Filley, A.; Shepherd, J.; Smith, S. (Peak Performance, 2008)
What can we do, as athletes, to improve our biomechanics in ways proven to add efficiency and speed to our sports performance?